MINOCA: Myocardial infarction no obstructive coronary artery disease - Hooman Bakhshi; C. Michael Gibson (American Heart Journal Plus, 2023)
Myocardial infarction without obstructive coronary artery disease (MINOCA) is defined as myocardial infarction with mild or no obstructive coronary artery disease (CAD) on angiogram. MINOCA has a number of heterogeneous causes, including coronary disruption, coronary vasospasm, coronary embolism, spontaneous coronary artery dissection (SCAD), and coronary microvascular dysfunction (CMD). Even though MINOCA might have a better prognosis than MI with obstructive CAD, it is not benign. A stepwise diagnostic approach is crucial to identifying the underlying cause of MINOCA or conditions mimicking it. A cause-specific treatment approach is the key to managing MINOCA.